Criminal Law Policies In Overcoming Corruption In Indonesia Through Death Penalty In Relation To The Principle Of Justice - Herman Suherman (Fakultas Hukum, Universitas Islam Bandung, 2022)
Law of the Republic of Indonesia Number 31 of 1999 Juntco Law of the Republic of Indonesia Number 20 of 2001 concerning Eradication of Corruption Crimes still contains weaknesses in regulating death penalty. This research is a normative juridical research with the starting point of Article 2 paragraph (2) of the Corruption Crime Act. The approach in this writing uses a statutory approach (statute appoach). This study uses secondary legal materials with data collection methods used in literature studies. The results of the research found various reasons that make the implementation of death penalty stiff against perpetrators of corruption in Indonesia, therefore through criminal law policies it is necessary to reform the law. This legal renewal through a collaborative approach is based on the fact that law enforcement is a system that complements one another. These three are the legal substance aspect, the legal structure aspect, and the legal culture aspect.There are four reform models that can be carried out to deal with criminal acts of corruption, namely first, reforming legal institutions. Here, it is necessary to strengthen the authority and strengthen the professionalism of the apparatus that fills the legal institution, the police, prosecutors and the KPK must be able to work together and haveunified legal opinionregarding corruption cases, the most overt nature and sectoral ego in eradicating corruption must be eliminated. The main thing is the realization of a framework and a unified view of corruption cases. Second, reforming the legislation in the sense of re-evaluating, reorienting and reformulating the applicability of the Corruption Crime Law, both the formulation of the act and the system of sanctions, especially related to death penalty. Third, improvement in the community legal culture sector. It is no longer a legal secret that the Indonesian people are people who like to circumvent the law. With these three models of legal renewal, it is hoped that it is hoped that the handling of criminal acts of corruption through death penalty that fulfills a sense of justice can be realized.